Geo-Politics of the Euro-Asia Energy Nexus - Tekin, A. author. aut Link
XII, 230 p.
Keywords: A freshly provocative look at the nexus linking EU security, trans-Turkey energy supply routes to Europe and Turkey's EU membership negotiations, this book argues that Europe's collective energy security prospects have become increasingly tied to Turkey's progress towards joining the EU.